Impact of biomanufacturing protein fibers on achieving sustainable development - Benjamin D. Allen; Baljit Ghotra; Birgit Kosan; Philipp Köhler; Marcus Krieg; Christoph Kindler; Michael Sturm; Melik C. Demirel (Proceedings of the National Academy of Sciences, 2025)
Biomanufactured fibers produced through fermentation processes provide a promising pathway to decouple textile production from agricultural land. This would free up arable land for food cultivation and contribute to the United Nations Sustainable Development Goal 2: Zero Hunger. Protein fibers from natural sources such as cocoon silk, collagen, and soy have attracted attention since the last century. However, commercial production declined with the rise of cheaper synthetic fibers and competition for food crops. Recently, renewed interest in protein fibers has emerged as a means to minimize plastic pollution, fueled by advances in fermentation, even though challenges related to yield, costs, and industrial spinning persist. Here, we studied a lyocell-based technique for spinning protein fibers using yeast biomass purified through an enzymatic method. We demonstrated that the enzymatic approach produces insoluble proteins that can be continuously spun for over 100 h of production time. Pilot-scale production exhibited stable spinning behavior with high viscosity and consistency quality. We achieved fiber fineness between 1.7 and 2.2 dtex, with strength values reaching 23 cN/tex, which is 50% higher than those of natural protein fibers such as wool. Life cycle assessment indicates that fermentation-based protein fibers require significantly less land and water than natural fibers while providing a reduced environmental footprint. Techno-economic analysis indicates a cost of $6 per kilogram at a production rate of 6,750 t annually. Adopting biomanufacturing-based protein fibers marks a significant advancement toward a future where fiber needs are fulfilled without compromising the planet’s capacity to nourish its growing population.